Hemodynamics of the superior mesenteric artery and splenic artery in healthy subjects and patients with portal hypertension: Investigatin with duplex Doppler ultrassonography - Derya SARAÇYAKUPOĞLU; Ayşe ERDEN; Tülay ÖLÇER; Turhan CUMHUR (Turkish Journal of Gastroenterology, 2019)
-